Knowledge Management in Southeast Asia Countries Company - Diah Lutfiani; Tamara Adriani Salim; Frans Asisi Datang (Program Studi Ilmu Perpustakaan UIN Alauddin, 2023)
Knowing the connection between company’s success factor from knowledge management will be a great finding for other companies. The purpose of this research is to analyze how companies implement Knowledge Management (KM) based on the four KM lifecycles by Bukowitz and Williams The data comes from any scientific paper about the implementation of KM in companies in Southeast Asia from 2016 until 2022. This research utilized Systematic Literature Review (SLR) based on the PICOC methodology. This systematic literature review observes and identifies the KM implementation through the KM lifecycle. KM lifecycle consists of four cycles: get, use, learn, and contribute. The get stage consists of three main modes of implementation: company ways of seeking information to decide, company ways of seeking information to solve a problem, and company ways of seeking information to innovate. The use stage consists of two main modes of implementation: company ways of combining information in new/different ways and company ways of combining information in exciting practices. The learning stage consists of one primary mode of implementation: company ways of learning from experiences to create a competitive gain. The contribute stage consists of one primary mode of implementation: employee ways of dispatching their knowledge to the communal knowledge base.